Essentials of marketing research - Hair, Joseph F.; Celsi, Mary Welfinbarger; Ortinau, David J.; Bush, Robert P. (New York, NY McGraw-Hill/Irwin, 2013)
"Essentials of Marketing Research concisely delivers an up-to-date review of a broad variety of marketing research topics. It takes an application-oriented approach, providing students with the tools and skills necessary to solve business problems and exploit business opportunities. The authors' years of experience in real- world marketing research is evident throughout, from their thorough treatment of qualitative research (given short shrift in many other books) to their knowledgeable coverage of sample size rules-of-thumb, conducting a background literature review, and the importance of new market research tools and techniques. Essentials of Marketing Research gives students a strong command of market research principles, while being short enough to use alongside cases or projects."--Publisher's website.
Marketing Research for Managerial Decision Making -- The Marketing Research Process and Proposals -- Secondary Data, Literature Reviews and Hypotheses -- Exploratory and Observational Research Designs and Data Collection Approaches -- Descriptive and Casual Research Designs -- Sampling: Theory and Methods -- Measurement and Scaling -- Designing the Questionnaire -- Qualitative Data Analysis -- Preparing Data for Quantitative Analysis -- Basic Data Analysis for Quantitative Research -- Examining Relationships in Quantitative Research -- Communicating Marketing Research Findings
Includes bibliographical references and indexes.
Keywords: Marketing research